Upper aerodigestive tract cancer: summary of the National Institute for Health and Care Excellence guidelines for England and Wales. - Paleri, V; Kerawala, C; Winter, S; Robinson, M; Jarrom, D; Prettyjohns, M (Wiley, 2016)
The cancers of the upper aerodigestive tract (CUADT) considered in this guideline document include the oral cavity, oropharynx, nasopharynx, hypopharynx, larynx and paranasal sinus. Squamous cell carcinomas (SCC) are the predominant (91%) histological type of malignancies seen at these sites,with approximately 8500 people per annum being diagnosed with CUADT in England and Wales. This guideline deals with SCC and mucosal melanoma and applies to 94% of CUADT cancers. Between 1990 and 2006, the incidence of oropharyngeal cancer has doubled, oral cavity cancer showed a slight increase, whilst cases of larynx cancer have declined.1 Although the age and sex distribution varies across primary sites, SCCs are commoner in men with incidence starting at the age of 40, and peaking after the age of 60. The aetiologic factors associated with CUADT are smoking, alcohol, human papillomavirus (oropharynx only) and certain occupations.